2017
DOI: 10.1177/0030727017742557
|View full text |Cite
|
Sign up to set email alerts
|

Productivity change analysis in dairy farms following Polish accession to the EU – An output growth decomposition approach

Abstract: The aim of this study was to assess changes in productivity of dairy farms after Poland’s accession to the European Union using a new decomposition of output growth within a stochastic frontier framework. We demonstrate how changes in economies of scale can be isolated, which leads to redefined components of output growth and a better measure of productivity growth. The productivity component is disaggregated to its three generic sources: total scale change, real technical change and efficiency change. An anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…The average technical efficiency score obtained from the GTRE model is lower than in the previous studies of Polish dairy farms (Čechura et al, 2017;Pisulewski, 2017 or Makieła, Marzec, and. However, the above-mentioned studies distinguish only one type of inefficiency.…”
Section: Discussioncontrasting
confidence: 58%
“…The average technical efficiency score obtained from the GTRE model is lower than in the previous studies of Polish dairy farms (Čechura et al, 2017;Pisulewski, 2017 or Makieła, Marzec, and. However, the above-mentioned studies distinguish only one type of inefficiency.…”
Section: Discussioncontrasting
confidence: 58%
“…Labor input is defined as "total number of hours worked annually" in a given country (in thousands). All variables have been mean-corrected, which means that parameters of the first order approximation (β 2 , β 3 ) are interpreted as elasticities at the sample mean; see, e.g., (Makieła et al 2017).…”
Section: Results Based On Dataset Amentioning
confidence: 99%
“…Various studies on farm productivity in Poland (Makieła et al, 2017;Pisulewski, 2017, 2019;Smędzik-Ambroży et al, 2019) and Cunha and Swinbank (2011) found that contrarily DPs did not reduce market uncertainties on farmers' incomes. Original scientific paper DOI: /10.5513/JCEA01/24.2.3656 Barma: Trends and determinants of post-integration agricultural transformation in Poland and...…”
Section: Farm Competitivenessmentioning
confidence: 99%